Refugee economies in Kenya - Betts, A; Sterck, O; Omata, N (Refugee Studies Centre, 2018)
Kenya currently hosts 490,000 refugees. Most are Somali refugees but others are from South Sudan, Ethiopia, the Great Lakes region, and Sudan. Its refugees are concentrated in three main locations: the Dadaab camps, the Kakuma camp, and Nairobi. Since the early 1990s, the Government of Kenya has restricted refugees’ socio-economic freedoms, notably by denying them the right to work and limiting their movement outside of camps. Kenya therefore represents an interesting context in which to examine the economic lives of refugees and their interactions with host communities within a constrained regulatory environment, typical of many refugee-hosting countries. The distinctive regulatory environment faced by refugees enables us to explore a particular and under-researched question: ‘What difference does it make – in economic terms – to be a refugee?’ In order to explore this, we collect quantitative and qualitative data from both refugees and host communities, in both urban and camp contexts. The report represents the first systematic comparison of economic outcomes for refugees and host communities. It draws upon the baseline data collection we have conducted in Kenya as part of a broader multi-country, multi-year panel dataset.